Income distribution theory - Bronfenbrenner, Martin (London : Macmillan, 1971)
This book treats the economies of the distribution of income. The subject was the heart of Ricardo's contribution to the development of English classical economics and the backbone of the science of economics until contemporary times.
Includes bibliographical references and index.
osa 03/08/2017
Loans
Keywords: Income distribution; Wealth